From market to hierarchy: An empirical assessment of a supply chain governance typology. Issue 1 (January 2018) - Ashenbaum, Bryan
Abstract: This study performs an empirical assessment of the highly influential supply chain governance typology put forth in Gereffi et al. (2005). In spite of the influence this Global Value Chain (or GVC) Typology has had, there have been few (if any) attempts to empirically assess its alignment with real-world supply chain structures and to establish a baseline for its predictive utility. The GVC Typology is assessed for face and nomological validity through testing of its key dimensions in relation to purchasing-logistics integration and supplier performance measures, using an information-processing theory framework. The GVC Typology appears to have considerable face validity as actual supply chain governance structures aligned well with those it proposes. It also has reasonable predictive power with regards to governance dimensions and integration, and in some connections between governance types, integration, and supplier performance. This study provides researchers with the tools to move this typology beyond the "conceptual" stage in their work, allowing for holistic and higher-level assessments of supply chain governance structures and changes. It may also help researchers and managers to consider when and to what extent purchasing-logistics integration should be fostered. Highlights: This study performs an empirical assessment of the GVC Typology put forth inGereffi et al. 2005 . Actual supply chain governance structures aligned well with those proposed by the GVC typology. The GVC Typology has reasonable predictive power for integration and supplier performance. The GVC Typology aids researchers interested in holistic supply chain research questions. The study provides managers a roadmap to properly assess their supply chains.